Using the health belief model to determine differences in university foodservice employees' beliefs and perceptions about handwashing and foodborne illness - Bolte, Becky J. (Kansas State University, 2013)
The Centers for Disease Control estimates that each year 48 million Americans become ill, 128,000 are hospitalized, and 3,000 die of foodborne diseases. In 2011, the CDC reported that Norovirus caused the majority of all foodborne diseases and can be eliminated with proper handwashing, which is the number one way to prevent the spread of foodborne disease. The purpose of this study was to use the Health Belief Model to determine differences in university foodservice employees’ beliefs and perceptions about handwashing and foodborne illness. The constructs of perceived susceptiblity, severity, barriers, benefits, and self-efficacy as they relate to handwashing were used to examine the differences in demographics. Instrument development included a review of literature, focus group feedback, a pilot study and a review by industry experts. The final instrument was distributed to all foodservice employees at Kansas State University using Qualtrics and pen-and-paper surveys. Frequencies, means, t-tests, ANOVA, and regression were used for data analysis and to answer research questions. Results indicated respondents who were older (above 23 years of age), full-time employees, had more than three years of experience, and were food safety certified had a higher perception of susceptibility, benefits, and self-efficacy of handwashing and its relationship to reducing foodborne illness. Perceived severity was highest among respondents with food safety certification and more than three years of experience. Supervisor/Manager category did not agree on barriers to handwashing in the workplace with other positions; however, most employees did not rate barriers as a problem. Non-white respondents showed a lower self-efficacy for ability to wash hands correctly. Results of this study highlight the need for self-efficacy focused handwashing training for first year and non-white employees.
Keywords: Food Safety; University foodservice employees; Health belief model; Handwashing; Foodborne illness; Food Science (0359); Health Education (0680); Management (0454)